2013
DOI: 10.5120/13546-1339
|View full text |Cite
|
Sign up to set email alerts
|

Do Aesthetics Matter in Long-Established Trust?

Abstract: Recently trust has gained momentum in user experience (UX) research due to the rapid development of e-commerce services, privacy and security issues. It is widely considered that the perception of trust is not only influenced by the website attributes (i.e., usability, functionality), but also by other human factors such as aesthetics. However, it is not clear that which factors of aesthetics influence what dimensions of trust while considering aesthetics and trust as multidimensional constructs. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…This consequently increases their return visits and retains them as users (and ultimately as customers). The outcomes of this study are also consistent with the findings reported in the literature by Turkyilmaz et al (2015) in affirming the effect of aesthetics on UX and its role in increasing customer satisfaction and sales through providing ease of use and enjoyment for users, and by Hasan et al (2013) where the aesthetics of UX were found to influence the perception of trust.…”
Section: Structural Framework and Hypotheses Testingsupporting
confidence: 92%
“…This consequently increases their return visits and retains them as users (and ultimately as customers). The outcomes of this study are also consistent with the findings reported in the literature by Turkyilmaz et al (2015) in affirming the effect of aesthetics on UX and its role in increasing customer satisfaction and sales through providing ease of use and enjoyment for users, and by Hasan et al (2013) where the aesthetics of UX were found to influence the perception of trust.…”
Section: Structural Framework and Hypotheses Testingsupporting
confidence: 92%